Peningkatan Pemahaman Konsep Matematika Pada Siswa SD dengan Menggunakan Model Teams Games Tournament (TGT) - Yenny Royani; Jajang Bayu Kelana (EduBase : Journal of Basic Education, 2022)
This research is motivated by the low understanding of the concept of learning mathematics in elementary schools. In addition, it is known that there are many problems that occur in learning mathematics. The purpose of this study was to determine the scenario and implementation of understanding mathematical concepts using the TGT model, student responses, and the difficulties experienced by students. The research method used is descriptive qualitative. The subjects in this study were third grade students of SD Prasistha in Bandung City with a total of 10 students consisting of 4 female students and 6 male students. The results showed that there was an increase in the quality of learning when the TGT model was applied. Thus, it can be concluded that the results of the study show the scenario and implementation of learning as indicated by the average result of the respondents' attitudes of 71% which are included in the good category. And the difficulties experienced by students with an average of 26% contained in the concept understanding indicator. Abstrak Penelitian ini dilatarbelakangi oleh rendahnya pemahaman konsep pada pembelajaran matematika di sekolah dasar. Selain itu diketahui banyaknya permasalahan yang terjadi pada pembelajaran matematika. Tujuan penelitian ini untuk mengetahui skenario dan implementasi pemahaman konsep matematika dengan menggunakan model TGT, respon siswa, serta kesulitan-kesulitan yang dialami seswa. Metode penelitian yang digunakan adalah deskriptif kualitatif. Subjek dalam penelitian ini adalah siswa kelas III SD Prasistha di Kota Bandung dengan jumlah siswa sebanyak 10 orang yang terdiri dari 4 orang siswa perempuan dan 6 orang siswa laki-laki. . Hasil penelitian menunjukkan bahwa terdapat peningkatan kualitas pembelajaran ketika diterapkannya model TGT. Dengan demikian dapat disimpulkan bahwa hasil penelitian menunjukkan skenario dan implementasi pembelajaran ditunjukkan dengan hasil rata-rata responden sikap siswa sebesar 71% yang termasuk kategori baik. Dan kesulitan yang dialami siswa dengan rata-rata 26% yang terdapat pada indikator pemahaman konsep.